KRITERIA DIAGNOSIS DAN DIAGNOSIS BANDING SUDDEN DEAFNESS (SSNHL) - Arvindan Subramaniam (DiscoverSys Inc., 2016)
Introduction: Sudden deafness or sudden sensorineural hearing loss (SSNHL) is defined as sensorineural hearing loss of more than 30 dB at three consecutive frequencies within 3 days of onset, often unilateral and idiopathic. Etiology of sudden deafness is still not known, but there are many theories put forward by the experts as a risk factor for sudden deafness. The prevalence of sudden deafness 5-30 per 100,000 people per year. Distribution of men and women almost equally, with the peak age of 50-60 years. Sudden deafness diagnosis is made based on history, physical examination and audiometry. Sudden deafness has three characteristics; acute, sensorineural hearing loss and unknown etiology. Additional characteristics may include vertigo, tinnitus and the absence of cranial nerve involvement. Management of sudden deafness include conservative therapy with multiple modalities.Case: Patient male, 40 years, Bali, Hindu present with hearing loss since ± 2 weeks ago. Patients previously complained of heat in the ear ± 2 days ago accompanied by a downward hearing and ears. A history of vomiting, coughs and colds denied. History of treatment at the hospital and was hospitalized for ± 2 weeks. Patients had never suffered from the same disease. No history of sinusitis, allergy, anemia, autoimmune and other systemic diseases. Patients also had never experienced trauma and underwent nasal surgery before.